Metabolomics analysis of salvage chemotherapy on refractory acute myeloid leukemia patients. Issue 26 (18th April 2018) - Zheng, Zhi; Liu, Pingyi; Xu, Liting; Peng, Zhiqiang; Zhang, Yayue; Chen, Xinyi; Hou, Li; Cui, Wenhao; Tou, Fangfang; Rao, Jun; Fan, Xing
Abstract : Salvage chemotherapy had minimal impact on the metabolomics for individual RAML patient. Abstract : Acute myeloid leukemia (AML) is a group of hematological malignancies causing high mortality around the world. However, the treatment of AML is still one of the most formidable challenges. In this study, we employed a well-established global metabolic profiling platform, which combined ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) with gas chromatography mass spectrometry (GC-MS) to investigate the metabolic alterations associated with salvage chemotherapy on 10 refractory acute myeloid leukemia (RAML) patients. A total of 390 metabolites were identified from 20 serum samples obtained from all 10 patients before and post salvage chemotherapy. The metabolomics profile was found to be very heterogeneous across the RAML patients. The results showed very subtle metabolic differences upon one-time chemotherapy treatment for an individual patient. Only 9 metabolites including imidazole lactate, glycerol 3-phosphate, three fatty acids, and four lysolipids in the blood serum were significantly changed before and post chemotherapy, suggesting their important roles during the development of RAML. This study may not only provide new insight into the metabolomics features in RAML patients, but also have relevance to improve the treatment and outcome of RAML.